Scaling Imagination: The Language Machine and Poetry - Winiecka, Elżbieta (Przestrzenie Teorii, 2024)
The article focuses on the specificity and functions of metaphors in the poetry of Radosław Jurczak, and more broadly in the work of the youngest poets, for whom life in the world of digital media and the prospect of the development of artificial intelligence is an important part of their formative experience. The paper uses the terms introduced by Mark Fisher for this purpose: the weird and the eerie. The analysis compares poetic devices in Jurczak’s poems with the concept of poetic language of the first avant-garde, pointing out the changes occurring in the poetics and aesthetics of the works, also focusing on figures relating to the technological sphere of modernity. The paper polemizes with the view expressed by Jerzy Jarzębski, who considers the phrase “artificial intelligence” to be a fashionable and harmful oxymoron that defines the pragmatic, reductionist worldview of its users. The article argues that the incorporation of terms that have the status of catachreses and over-lexicalized metaphors in everyday language into the language of poetry allows their creative potential and ambiguity to be recovered. Finally, the paper considers scaling as a characteristic feature of the new poetic imagination, which also requires readers to take a new approach to the language of the new poetry.